Plutarch on Demetrius of Phalerum: the Intellectual, the Legislator and the Expatriate - Leão, Delfim (2018)
Throughout the Lives and the Moralia, Plutarch regularly mentions the work, the activity or even the exemplum of Demetrius, both as a source of information on others and as a very stimulating character per se. From those passages emerges the figure of Demetrius as the intellectual, the politician and the legislator, and finally that of the expatriate fallen in disgrace, who was nevertheless able to recover his vitality and influence in the court of the Ptolemies.